PERBEDAAN PROSES PEMBELAJARAN DAN PRESTASI BELAJAR SISWA SD EKS-RSBI DAN SDSN DI DIY - Herjan Haryadi; Heri Retnawati (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2014)
Penelitian ini bertujuan untuk mengetahui perbedaan proses pembelajaran dan prestasi belajar siswa eks-RSBI dan SDSN di DIY pada mata pelajaran matematika, IPA dan Bahasa Indonesia. Penelitian ini merupakan studi penelitian komparasi. Populasi dalam penelitian ini adalah seluruh siswa kelas IV dan V SD eks-RSBI dan SDSN di DIY. Analisis data menggunakan (1) statistik deskriptif untuk mendeskripsikan proses penelitian dan menggambarkan mean dari data yang diperoleh; dan (2) statistik inferensial menggunakan uji multivariat (Manova) dan uji univariat dengan uji t untuk menguji hipotesis penelitian dengan taraf signifikansi 5%. Hasil penelitian menunjukkan bahwa. (1) tidak terdapat perbedaan proses pembelajaran dan prestasi belajar matematika antara siswa SDSN dan SD Eks-RSBI di DIY, (2) terdapat perbedaan proses pembelajaran dan prestasi belajar IPA antara siswa SDSN dan SD Eks-RSBI di DIY, (3) terdapat perbedaan proses pembelajaran dan prestasi belajar Bahasa Indonesia antara siswa SDSN dan SD Eks-RSBI di DIY.A COMPARATIVE OF THE LEARNING PROCESS AND ACHIEVEMENT GRADE STUDENTS OF EX-RSBI ELEMENTARY SCHOOLS AND NATIONAL STANDARD ELEMENTARY SCHOOLS IN DIYABSTRACTThis study intends to know the differences in the learning process and learning achievement of the fourth and the fifth grade studentsofex-RSBI elementary schools (SD) and national standard elementary schools (SDSN) in Yogyakarta Special Territory (DIY)in learning mathematics, science, and Indonesian. This study is a comparative study. The population of this study is the fourth and the fifth grade students of the ex RSBI SD and SDSN in DIY. The data were analyzed using (1) descriptive statistics, to describe the process of the research and to describe the mean, median, and standard deviation of the collected data; and (2) inferential statistics by using the multivariate test (Manova) and univariate test using t-test to test the hypothesis with the significance level of 5%. The result shows that. (1) there is no difference in the learning process and achievement in mathematics among the students of SDSN and those of ex-RSBI SD in DIY, (2) there is a difference in the learning process and achievement in science among the students ofSDSN and those of ex-RSBI SD in DIY,(3) there is a difference in the learning process and achievement in Indonesian among the students of SDSN and those of ex-RSBI SD in DIY.Keywords: learning process, learning achievement